Operation effect to voltage SAG Immunity Levels of AC Contractors at petrochemical plant in Pahang, Malaysia - Khalis, Mokhtar; Hazri Dahalan, Md Razip; Effinizam, Abdul Latip (CIRED Repository, 2019)
Frequent voltage sag events at Gebeng Industrial Area posed a significant impact on the process lines of a petrochemical plant. Several of its important electrical/electronic equipment which is controlled by AC contactors had tripped, resulting in long downtime and high losses. In order to understand this power quality issue, the plant had collaborated with TNB Energy Services, a wholly owned subsidiary of Tenaga Nasional Berhad to evaluate its equipment immunity levels with respect to voltage sag. This paper aims to study and compare the immunity level of the AC contactor which is used in industrial operation over period of time. The contactors were sampled randomly and test was conducted at site. The response is benchmarked against Malaysian Standard MS IEC 61000-4-11 voltage tolerance curve. Subsequently the result for test conducted within period of four (4) years is presented. Three out of five AC contactors show weakening of immunity levels and four out of five contactors exhibit an increase of exposure level when compared with actual power quality data. Finally, the options of improvement to ensure high ride through capability is propose